Identification of Candidate Genes for Salinity and Anaerobic Tolerance at the Germination Stage in Rice by Genome-Wide Association Analyses - Islam, Mohammad Rafiqul; Naveed, Shahzad Amir; Zhang, Yue; Li, Zhikang; Zhao, Xiuqin; Fiaz, Sajid; Zhang, Fan; Wu, Zhichao; Hu, Zhiqing; Fu, Binying; Shi, Yingyao; Shah, Shahid Masood; et al. (Frontiers in Genetics, 2022)
Multiple stress tolerance at the seed germination stage is crucial for better crop establishment in the direct-seeded rice ecosystem. Therefore, identifying rice genes/QTLs associated with salinity and anaerobic tolerance at the germination stage is a prerequisite for adaptive breeding. Here, we studied 498 highly diverse rice accessions Indica (Xian) and Japonica (Geng) and six traits that are highly associated with salinity and anaerobic tolerance at germination stage were measured. A high density 2.8M SNP genotype map generated from the 3K RGP was used for mapping through a genome-wide association study (GWAS). In total, 99 QTLs loci harboring 117 QTLs were detected in different populations, 54, 21 and 42 of which were associated with anaerobic, salinity and combine (anaerobic and salinity) stress tolerance. Nineteen were close to the reported loci for abiotic stress tolerance, whereas two regions on chromosome 4 (qSGr4a, qCL4c, qRI4d and qAGr4, qSGr4b) and one region on chromosome 10 (qRI10, qCL10, qSGr10b, qBM10) were associated with anaerobic and salinity related traits. Further haplotype analysis detected 25 promising candidates genes significantly associated with the target traits. Two known genes (OsMT2B and OsTPP7) significantly associated with grain yield and its related traits under saline and anaerobic stress conditions were identified. In this study we identified the genes involved in Auxin efflux (Os09g0491740) and transportation (Os01g0976100); while identified multi stress responses OsMT2B gene (Os01g0974200) and a major gene OsTPP7 (Os09g0369400) involved in anaerobic germination and coleoptile elongation on chromosome 9. These promising candidates provide valuable resources for validating potential salt and anaerobic tolerance genes, and will facilitate direct-seeded rice breeding for salt and anaerobic tolerance through marker-assisted selection or gene editing.